Optical film and display device
Patent Information
- Application Number
- KR1020267021422
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-01-22
- Filing Date
- 2025-01-17
- Publication Date
- 2026-09-01
Smart Images

Figure PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to an optical film and a display device having the optical film. Background Technology
[0002] Optical films have the function of controlling actions such as light reflection or transmission. For example, an optical film is placed on the surface of a display device for the purpose of making the screen of the display device easy to view.
[0003] In addition to optical properties such as haze, optical films require various properties such as hardness and scratch resistance depending on the application. Furthermore, due to the recent increase in hygiene awareness, the demand for optical films with antibacterial and antiviral properties is also rising. To impart antibacterial and antiviral properties to an optical film, an antibacterial and antiviral agent can be added to the resin constituting the optical film. As antibacterial and antiviral agents, metal-based particles containing silver or silver compounds are widely used (see, for example, Patent Document 1). Prior art literature
[0004] Japanese Patent Publication No. 6720639 The problem to be solved
[0005] When an optical film contains metal-based particles as an antimicrobial and antiviral agent, increasing the content of the metal-based particles increases light scattering on the surface or within the optical film, which tends to increase haze. Therefore, there are limitations on the content of metal-based particles when trying to obtain desired optical properties in an optical film. In particular, for types of optical films characterized by high transparency, such as those requiring a haze of 1% or less, it is difficult to achieve both antimicrobial and antiviral properties and optical properties simultaneously. Furthermore, regulations regarding the use of silver-based antimicrobial and antiviral agents are also being strengthened in Europe.
[0006] Meanwhile, among compounds usable as antimicrobial and antiviral agents, there are organic materials such as quaternary ammonium salts in addition to metal particles. Since organic antimicrobial and antiviral agents are not in the form of particles, they are less likely to cause an increase in haze. However, generally, while curable resins, which are the main components of optical films, are hydrophobic to improve the strength or hardness of the film, most organic antimicrobial and antiviral agents are hydrophilic. Therefore, if a layer in which an organic antimicrobial and antiviral agent is mixed with the curable resin is formed as a constituent layer of an optical film, phase separation occurs during the curing of the layer, and bleed-out occurs. means of solving the problem
[0007] Each embodiment of an optical film and a display device for solving the above problem is described.
[0008] [Aspect 1] An optical film comprising a substrate and a functional layer containing a functional component which is at least one of an antibacterial agent and an antiviral agent and a resin component, wherein the functional component is an organic material, the ratio of the functional component to the resin component contained in the functional layer is 40 mass% or less, and the average hydroxyl value of the resin component is 100 mgKOH / g or more, which is a first condition, and the water vapor permeability per unit film thickness in the functional layer is 170 (g / m²·day) / ㎛ or more, and the optical film satisfies at least one of the first condition and the second condition.
[0009] According to the above composition, at least one of antibacterial and antiviral properties can be obtained, and the rise of haze and the occurrence of bleed-out in the functional layer can be suppressed.
[0010] [Aspect 2] An optical film described in [Aspect 1] that satisfies the above-mentioned first condition and has an average hydroxyl value of the resin component of 200 mgKOH / g or less.
[0011] According to the above configuration, the degradation of mechanical properties such as strength in the functional layer can be suppressed.
[0012] [Embodiment 3] An optical film described in [Embodiment 1] or [Embodiment 2], wherein the polymer constituent unit containing the resin component comprises a first constituent unit that does not have a hydroxyl group and a second constituent unit that has one or more hydroxyl groups, and the ratio of the second constituent unit to all constituent units in the resin component is 0.40 or higher.
[0013] According to the above configuration, the occurrence of bleed-out in the functional layer can be suitably suppressed.
[0014] [Aspect 4] An optical film described in any one of [Aspect 1] to [Aspect 3], wherein the haze of the optical film is 3% or less.
[0015] According to the above composition, high transparency can be obtained. Also, since the functional component is organic, it is easy to reduce the haze to 3% or less.
[0016] [Aspect 5] The optical film described in any one of [Aspect 1] to [Aspect 4] comprises a resin layer supported on the substrate, the functional layer comprises the resin layer, and the resin layer comprises fine particles for light scattering.
[0017] According to the above configuration, an optical film having anti-glare properties can be realized.
[0018] [Embodiment 6] An optical film described in [Embodiment 5], wherein the average particle size of the above-mentioned fine particles is 30% or more of the thickness of the above-mentioned resin layer.
[0019] According to the above configuration, the effect of light scattering by fine particles can be suitably obtained.
[0020] [Embodiment 7] An optical film described in [Embodiment 5] or [Embodiment 6], wherein the content ratio of the fine particles in the resin layer is 3.0 mass% or more and 20 mass% or less.
[0021] According to the above configuration, the effect of light scattering by fine particles is suitably obtained, and at the same time, the deterioration of the mechanical properties of the resin layer can be suppressed.
[0022] [Aspect 8] An optical film described in any one of [Aspect 1] to [Aspect 7], wherein the pencil hardness of the surface of the optical film is 2H or higher.
[0023] According to the above configuration, good mechanical characteristics can be obtained.
[0024] [Embodiment 9] An optical film described in any one of [Embodiment 1] to [Embodiment 3], [Embodiment 5] to [Embodiment 7], wherein the haze of the optical film is 5% or more and 35% or less.
[0025] According to the above configuration, good anti-fouling properties can be obtained.
[0026] [Embodiment 10] An optical film described in any one of [Embodiment 1] to [Embodiment 3], [Embodiment 5] to [Embodiment 7], [Embodiment 9], wherein the reflection clarity at 1° is 90 or less and the reflection clarity at 5° is 60 or more.
[0027] According to the above configuration, good anti-fouling properties can be obtained.
[0028] [Embodiment 11] An optical film described in any one of [Embodiment 1] to [Embodiment 10], wherein the optical film comprises a resin layer supported on the substrate, the functional layer comprises the resin layer, and the thickness of the resin layer is 1.0 μm or more.
[0029] According to the above configuration, the uniformity of the resin layer thickness, the porosity of the coating solution for forming the resin layer, the mechanical strength of the resin layer, and the antibacterial or antiviral activity when the resin layer is a functional layer can be enhanced.
[0030] [Aspect 12] The optical film described in any one of [Aspect 1] to [Aspect 11] comprises a resin layer supported on a substrate and a low-refractive-index layer covering the resin layer on the side opposite to the substrate, the low-refractive-index layer having a lower refractive index than the resin layer, and the functional layer comprises at least the resin layer among the resin layer and the low-refractive-index layer, and the thickness of the low-refractive-index layer is 30 nm or more and 300 nm or less.
[0031] According to the above configuration, it is easy to generate light interference, and it is also easy to obtain good scratch resistance or adhesion to the resin layer.
[0032] [Aspect 13] The above functional component is a silane coupling agent containing a quaternary ammonium salt in its molecular structure, and the quaternary ammonium salt contains a halide ion, an optical film described in any one of [Aspect 1] to [Aspect 12].
[0033] According to the above composition, it is suitable as a functional component of an organic system.
[0034] [Aspect 14] The optical film described in [Aspect 13] has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and in elemental analysis of the first surface by X-ray photoelectron spectroscopy, the elemental concentration of N is 0.80 atm% or more and 4.00 atm% or less, the elemental concentration of Si is 0.75 atm% or more and 4.50 atm% or less, and the elemental concentration of halogen elements is 0.35 atm% or more and 2.90 atm% or less.
[0035] According to the above composition, both antibacterial and antiviral properties are obtained well, while bleed-out in the functional layer can be suppressed.
[0036] [Aspect 15] The optical film described in [Aspect 13] has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and in elemental analysis of the first surface by energy-dispersive X-ray spectroscopy, the elemental concentration of Si is 0.20 atm% or more and 1.30 atm% or less, and the elemental concentration of a halogen element is 0.19 atm% or more and 1.40 atm% or less.
[0037] According to the above composition, both antibacterial and antiviral properties can be obtained well, while bleed-out in the functional layer can be suppressed.
[0038] [Aspect 16] The optical film described in [Aspect 13] has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and the amount of halogen element elution from the first surface measured by ion chromatography is 4.0 nmol / cm² or more and 55.0 nmol / cm² or less.
[0039] According to the above composition, both antibacterial and antiviral properties can be obtained well, while bleed-out in the functional layer can be suppressed.
[0040] [Aspect 17] A display device comprising an optical film described in any one of [Aspect 1] to [Aspect 16], wherein the optical film is positioned on a display surface on which an image is displayed.
[0041] According to the above configuration, good optical and mechanical properties can be obtained along with antibacterial or antiviral properties near the surface of the display device. Effects of the invention
[0042] According to the present disclosure, in an optical film, at least one of antibacterial and antiviral properties can be obtained, and the rise of haze and the occurrence of bleed-out can be suppressed. Brief explanation of the drawing
[0043] FIG. 1 is a drawing showing the cross-sectional structure of a first example in an optical film of one embodiment. FIG. 2 is a drawing showing the cross-sectional structure of a second example in an optical film of one embodiment. FIG. 3 is a drawing showing the configuration of a display device of one embodiment. Specific details for implementing the invention
[0044] An embodiment of an optical film and a display device is described with reference to the drawings.
[0045] [Layer composition of optical film: Example 1]
[0046] FIG. 1 illustrates a first example of the layer configuration of an optical film (10). An optical film (10A), which is an optical film (10) of the first example, comprises a substrate (20) and a resin layer (21). The resin layer (21) is supported by the substrate (20). In the first example, the resin layer (21) contains a resin component and a functional component having at least one of antibacterial and antiviral properties. And, the surface of the resin layer (21) opposite to the surface in contact with the substrate (20) is the surface of the optical film (10A). The surface of the optical film (10A) is an active surface that exhibits antibacterial and antiviral action as an example of a first surface. The surface of the optical film (10A) opposite to the first surface is the second surface, and the second surface is the surface of the substrate (20). In the first example, the resin layer (21) corresponds to a functional layer containing functional components.
[0047] The composition of each layer is explained in detail below.
[0048] <Recording>
[0049] The material and thickness of the substrate (20) may be such that a resin layer (21) can be formed on the substrate (20). The substrate (20) is, for example, a resin film that is transparent to light in the visible region. Examples of materials for the resin film include polyester, polypropylene, polystyrene, nylon, polycarbonate, polyacrylonitrile, polyimide, triacetylcellulose, etc. The thickness of the substrate (20) is preferably 12 μm or more, and more preferably 20 μm or more, from the perspective of facilitating handling of the substrate (20). If the thickness of the substrate (20) is 12 μm or more, it is easy to obtain good strength or quality of the substrate (20). The substrate (20) may be a single-layer structure or a multi-layer structure.
[0050] <Resin layer>
[0051] The functional component included in the resin layer (21) is a hydrophilic organic material. Also, the form of the functional component is not particulate. The functional component may be a component that functions as either an antibacterial agent or an antiviral agent, or a component that functions as both an antibacterial agent and an antiviral agent, or a component whose function as an antibacterial agent or an antiviral agent changes depending on conditions such as the amount added.
[0052] In addition, in this embodiment, a functional component is defined as hydrophilic if it can be uniformly dissolved or dispersed when 10 g of water is added to 100 g of a functional component.
[0053] Specific examples of functional components include quaternary ammonium salts, triclosan, biguanide, chitosan, terpenes, hinokitiol, etc. For example, the functional component may be a silane coupling agent containing a quaternary ammonium salt in its molecular structure as a functional group that reacts with organic materials.
[0054] The mass ratio of the functional component to the resin component of the resin layer (21) is 40 mass% or less. Accordingly, bleed-out during the formation of the resin layer (21) caused by an excessive amount of the functional component is suppressed.
[0055] The mass ratio of the functional component to the resin component of the resin layer (21) is preferably 3 mass% or more and more preferably 5 mass% or more from the perspective of increasing antibacterial or antiviral activity. The mass ratio of the functional component to the resin component of the resin layer (21) is preferably 30 mass% or less and more preferably 20 mass% or less from the perspective of increasing the dispersibility of the functional component.
[0056] By using a non-particulate functional component, even if the resin layer (21) contains a functional component, the increase in haze of the optical film (10A) can be avoided.
[0057] The resin component contained in the resin layer (21) may be a UV-curing resin or a heat-curing resin. A UV-curing resin is a cured body of a photopolymerizable compound. Examples of photopolymerizable compounds are monofunctional, difunctional, or trifunctional (meth)acrylate compounds or urethane (meth)acrylate compounds. Also, "(meth)acrylate" is a general term for acrylates and methacrylates. Examples of heat-curing resins include acrylic resin, urethane resin, epoxy resin, etc. The resin component contained in the resin layer (21) may be one type or two or more types.
[0058] The resin layer (21) satisfies at least one of the following first and second conditions.
[0059] Condition 1: The average hydroxyl group of the resin component contained in the resin layer (21) is Hv 100 mgKOH / g or higher.
[0060] Second condition: The water vapor permeability Wx per unit film thickness of the resin layer (21) is 170 (g / m²·day) / ㎛ or more.
[0061] Below, each of the first condition and the second condition will be explained in detail.
[0062] (First condition)
[0063] The first condition is that the average hydroxyl group Hv of the resin component contained in the resin layer (21) is 100 mgKOH / g or higher. The average hydroxyl group Hv is a measured value obtained in accordance with JIS K0070 using the resin layer (21) or the material as a sample, or a calculated value obtained from the hydroxyl group of the material that is already known.
[0064] For example, if the resin component is a polymer produced from multiple types of monomers, the average hydroxyl group Hv is obtained by calculating the product of the hydroxyl group and the mole fraction of each monomer, and by calculating the sum of the products for all monomers. The mole fraction of a monomer is the ratio of the amount of that monomer to the total amount of monomers. In addition, each of these monomers is either a monomer that does not have a hydroxyl group or a monomer that has a hydroxyl group that does not contribute to the polymerization reaction.
[0065] In addition, for example, when a resin component contains multiple polymers and the hydroxyl value of each polymer is already known, the average hydroxyl value Hv is obtained by calculating the product of the hydroxyl value and the mole fraction of each polymer for each polymer, and by calculating the sum of the products for all polymers. The mole fraction of a polymer is the ratio of the amount of that polymer to the total amount of polymers, and for each polymer, the value obtained by dividing the mass of the polymer by the number average molecular weight is treated as the amount of the polymer.
[0066] Since the average hydroxyl group Hv is 100 mgKOH / g or higher, affinity between the resin component and the functional component can be obtained, so phase separation and bleed-out during the formation of the resin layer (21) is suppressed.
[0067] In addition, it is preferable that the average hydroxyl group Hv be 200 mgKOH / g or less. Accordingly, since there are no excessively many hydrophilic groups in the resin component, the deterioration of mechanical properties such as strength and hardness of the resin layer (21) is suppressed.
[0068] (Second condition)
[0069] The second condition is that the water vapor permeability Wx per unit film thickness of the resin layer (21) is 170 (g / m²·day) / ㎛ or more. The water vapor permeability is determined in accordance with JIS Z0208 (method for testing moisture permeability of moisture-proof packaging materials (Cup method)). The measurement conditions for water vapor permeability are: temperature: 40 ℃, humidity: 90 % RH, test time: 24 hours.
[0070] For example, the water vapor transmittance Wx per unit film thickness of the resin layer (21) is determined based on the measurement of the water vapor transmittance of the optical film (10A) and the water vapor transmittance of the substrate (20) alone. Specifically, when the water vapor transmittance of the substrate (20) is WA and the water vapor transmittance of the optical film (10A), i.e., the water vapor transmittance of the laminate of the substrate (20) and the resin layer (21) is WB, the water vapor transmittance WX of the resin layer (21) is determined by the following (Equation 1).
[0071] WX=WA×WB / (WA-WB) ···(Equation 1)
[0072] In addition, the film thickness of the resin layer (21) is set to t, and the water vapor permeability Wx per unit film thickness of the resin layer (21) is calculated by the following (Equation 2).
[0073] Wx=WX / t ···(Equation 2)
[0074] The higher the water vapor permeability Wx, the higher the affinity of the resin component of the resin layer (21) to water. Since the water vapor permeability Wx is 170 (g / m²·day) / ㎛ or higher, good affinity between the resin component and the functional component is obtained, so phase separation and bleed-out during the formation of the resin layer (21) are suppressed.
[0075] In addition, the greater the water vapor permeability Wx, the easier it is for the hydrophilic functional component to pass through the resin layer (21) and appear on the surface of the optical film (10A). Because of this, the functional component is more likely to come into contact with bacteria or viruses and exhibit antibacterial or antiviral properties.
[0076] Water vapor permeability Wx is correlated with the mean hydroxyl group Hv, and as the mean hydroxyl group Hv increases, the water vapor permeability Wx tends to increase. By using a resin component with a high mean hydroxyl group Hv, the water vapor permeability Wx can be increased.
[0077] Meanwhile, the greater the water vapor permeability Wx, the smaller the cross-linked portion of the resin in the resin layer (21). Therefore, in order to suppress the deterioration of mechanical properties such as strength and hardness of the resin layer (21), it is preferable that the water vapor permeability Wx be 450 (g / m²·day) / ㎛ or less.
[0078] Other features of the resin layer (21) are further explained. The following features are applicable even if the resin layer (21) satisfies either the first condition or the second condition.
[0079] Preferably, the resin component comprises a first constituent unit that does not have a hydroxyl group and a second constituent unit that has one or more hydroxyl groups. A single constituent unit in the resin component refers to a structure derived from one molecule of monomer. When the resin component comprises multiple types of polymers, the constituent units of each polymer are included in the constituent units of the resin component. The resin component may include a polymer having the first constituent unit and the second constituent unit within one molecule, or may include a polymer in which one molecule consists only of the first constituent unit and a polymer having the second constituent unit within one molecule.
[0080] By including the first constituent unit and the second constituent unit in the resin component, the mechanical properties of the resin layer (21) are likely to be higher compared to the case where all of the constituent units of the resin component are the second constituent unit.
[0081] The first constituent unit is a structure derived from acrylate monomers that do not have hydroxyl groups, such as pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate. In addition, examples of polymers consisting solely of the first constituent unit are acrylic resins or urethane resins produced from these monomers.
[0082] The second constituent unit is a structure derived from an acrylate monomer having a hydroxyl group, such as, for example, pentaerythritol triacrylate, glycerin triacrylate, etc. In addition, an example of a polymer containing the second constituent unit is an acrylic resin or other hydrophilic resin produced from a monomer containing these monomers.
[0083] The composition ratio Rc, which is the ratio of the second constituent unit to all constituent units in the resin component, is preferably 0.40 or higher. When the resin component includes multiple types of polymers, all constituent units of the resin component means all constituent units in all polymers.
[0084] For example, if the resin component is a polymer produced from a first monomer that does not have a hydroxyl group and a second monomer that has a hydroxyl group, the composition ratio Rc is the mole fraction of the second monomer relative to the total monomer. That is, when the amount of the first monomer is A and the amount of the second monomer is B, the composition ratio Rc is expressed by B / (A+B). In addition, each of these monomers is either a monomer that does not have a hydroxyl group or a monomer that has a hydroxyl group that does not contribute to the polymerization reaction.
[0085] In addition, for example, if the resin component comprises a plurality of polymers and the composition ratio Rcp of each polymer is already known, the composition ratio Rc of the resin component is obtained by calculating the product of the composition ratio Rcp and the mole fraction of each polymer, and by calculating the sum of the said products for all polymers. The mole fraction of a polymer is the ratio of the amount of substance of said polymer to the total amount of polymer, and for each polymer, the value obtained by dividing the mass of the polymer by the number average molecular weight is treated as the amount of substance of the polymer.
[0086] Since the composition ratio Rc is 0.40 or higher, the ratio of the second composition unit is sufficiently obtained, and thus the affinity between the resin component and the functional component is suitably obtained. Meanwhile, it is preferable that the composition ratio Rc be 0.85 or lower. Accordingly, since the ratio of the first composition unit is sufficiently obtained, the deterioration of the mechanical properties of the resin layer (21) is suppressed.
[0087] The resin layer (21) may include fine particles for adjusting the light scattering properties in the optical film (10A). By including fine particles, the surface roughness of the optical film (10A) can be adjusted, and accordingly, the light scattering properties on the surface of the optical film (10A) can be controlled. Since the surface of the optical film (10A) has appropriate light scattering properties, it is possible to increase the diffuse reflection component in the reflected light from the surface of the optical film (10A) and suppress the specular reflection component, thereby suppressing the reflection of the surroundings on the optical film (10A).
[0088] In addition, light scattering properties within the resin layer (21) can be controlled by the inclusion of fine particles. By controlling light scattering properties on the surface of the optical film (10A) and within the resin layer (21), the haze of the optical film (10A) can be controlled, and accordingly, the transparency of the optical film (10A) can be adjusted. In this embodiment, as described above, since the functional component is an organic material rather than a particulate one, the haze of the optical film (10A) can be controlled without being affected by the content of the functional component.
[0089] The microparticles are organic microparticles or inorganic microparticles. The microparticles included in the resin layer (21) may be of one type, or two or more types in which at least one of the material and average particle size is different from each other. The average particle size of the microparticles is the median diameter (D50) based on volume. It is preferable that the average particle size of the microparticles be 30% or more of the thickness of the resin layer (21), and more preferable that it be 50% or more and 80% or less of the thickness of the resin layer (21). The thickness of the resin layer (21) is the film thickness of the portion of the resin layer (21) that does not contain microparticles in the thickness direction. If the average particle size of the microparticles is within the above range, the effect of light scattering by the microparticles is suitably obtained.
[0090] The content ratio of fine particles in the resin layer (21) is preferably 3.0 mass% or more and 20 mass% or less. If the content ratio of fine particles is 3.0 mass% or more, the effect of light scattering by the fine particles is suitably obtained. If the content ratio of fine particles is 20 mass% or less, the resin component is not excessively reduced, so the deterioration of the mechanical properties of the resin layer (21) is suppressed.
[0091] Organic microparticles are resin particles made of transparent resin materials such as, for example, acrylic resin, polystyrene resin, styrene-(meth)acrylic acid ester copolymer, polyethylene resin, epoxy resin, silicone resin, polyvinylidene fluoride, and polyfluoroethylene-based resin.
[0092] Inorganic fine particles can be used as materials to control the sedimentation or aggregation of organic fine particles. Examples of inorganic fine particles include silica fine particles, metal oxide fine particles, and mineral fine particles. Examples of silica fine particles include colloidal silica or silica fine particles surface-modified with reactive functional groups such as (meth)acryloyl groups. Examples of metal oxides constituting metal oxide fine particles include aluminum oxide, zinc oxide, tin oxide, antimony oxide, indium oxide, titanium dioxide, zirconium dioxide, etc. Examples of minerals constituting mineral fine particles include mica, synthetic mica, vermiculite, montmorillonite, iron montmorillonite, bentonite, beidelite, saponite, hectorite, stevensite, nontronite, magardiite, illite, carnemite, layered titanate, smectite, synthetic smectite, etc.
[0093] The resin layer (21) may contain various additives. Examples of additives include ultraviolet absorbers, antistatic agents, leveling agents, and thickeners. Depending on the content of the additives, the ultraviolet absorption function or antistatic function of the resin layer (21) can be expressed, and the coating properties or quality can be improved.
[0094] The thickness of the resin layer (21) is preferably 0.5 μm or more and more preferably 1 μm or more from the perspective of increasing the uniformity of the thickness of the resin layer (21), the porosity of the coating liquid for forming the resin layer (21), the mechanical strength of the resin layer (21), and the antibacterial or antiviral activity. The thickness of the resin layer (21) is preferably 10 μm or less and more preferably 5 μm or less from the perspective of increasing the adhesion of the resin layer (21) to the substrate (20) and reducing the load required for curing the resin layer (21).
[0095] Also, the thickness of the resin layer (21) is the film thickness of the portion of the resin layer (21) that does not contain fine particles in the thickness direction. The thickness of each layer constituting the optical film (10) and the optical film (10) is the average value of the sample values of thickness in the cross-section of the object to be measured. The sample values of thickness are the measurements of thickness at 10 points spaced apart by 1 mm or more in the cross-section of the object to be measured, and the difference from the average value of these measurements is within 50% of the average value.
[0096] The resin layer (21) is formed by applying a resin layer coating solution, which is a coating solution for forming the resin layer (21), to the upper surface of the substrate (20), and curing the film formed thereby. The resin layer coating solution includes auxiliary agents as needed, such as compounds, functional components, and polymerization initiators, for forming the resin components of the resin layer (21). In the case of forming a resin layer (21) containing fine particles, the resin layer coating solution additionally includes fine particles.
[0097] Known methods such as bar coating, spin coating, offset coating, gravure coating, roll coating, and die coating can be used for the application of the resin layer coating solution. The curing method of the film after coating can be any method according to the curing type of the resin component, and ultraviolet irradiation or heat drying is used.
[0098] [Layer composition of optical film: Example 2]
[0099] FIG. 2 shows a second example of the layer configuration of an optical film (10). The optical film (10B), which is the optical film (10) of the second example, has a low refractive index layer (22) in addition to the substrate (20) and the resin layer (21). The low refractive index layer (22) has a lower refractive index than the resin layer (21) and has the function of suppressing surface reflection of the optical film (10B) by using light interference.
[0100] The low refractive index layer (22) is located on the resin layer (21). If the surface of the resin layer (21) has irregularities, the low refractive index layer (22) has a surface shape that follows the irregularities of the resin layer (21). In the second example, the side opposite to the surface in contact with the resin layer (21) in the low refractive index layer (22) is the surface of the optical film (10B). The surface of the optical film (10B) is an example of the first surface. As in the first example, the side opposite to the first surface in the optical film (10B) is the second surface, and the second surface is the surface of the substrate (20).
[0101] The low refractive index layer (22) comprises a UV-curing resin or a heat-curing resin. As such a resin component, the component exemplified as the resin component contained in the resin layer (21) may be used. Additionally, the low refractive index layer (22) may include a refractive index modifier to lower the refractive index of the low refractive index layer (22). The refractive index modifier is, for example, fluoride microparticles such as lithium fluoride, magnesium fluoride, sodium hexafluoroaluminate, or aluminum fluoride, or silica microparticles. As for the silica microparticles, using microparticles having internal pores, such as porous silica microparticles or hollow silica microparticles, is effective for lowering the refractive index of the low refractive index layer (22).
[0102] The low refractive index layer (22) may contain various additives. Examples of additives include ultraviolet absorbers, antistatic agents, leveling agents, and thickeners. By including additives, it is possible to achieve ultraviolet absorption or antistatic functions in the low refractive index layer (22), as well as improve coating properties and quality.
[0103] The low refractive index layer (22) is thinner than the resin layer (21). The average thickness of the low refractive index layer (22) is preferably 30 nm or more and 300 nm or less. If the average thickness of the low refractive index layer (22) is 30 nm or more, it is easy to cause light interference, and if the average thickness of the low refractive index layer (22) is 300 nm or less, it is easy to maintain good scratch resistance and adhesion to the resin layer (21).
[0104] In the optical film (10B) of the second example, at least one of the resin layer (21) and the low refractive index layer (22) contains a functional component. The layer containing the functional component corresponds to the functional layer. The functional layer containing the functional component satisfies at least one of the first condition and the second condition described in the first example, and it is also preferable that the resin component of the functional layer satisfies the condition described in the first example with respect to the composition ratio Rc.
[0105] As for the functional component, the component exemplified in the first example may be used. The mass ratio of the functional component to the resin component of the functional layer is 40 mass% or less. Also, the ratio of the functional component to the total mass of the resin layer (21) and the low refractive index layer (22) is preferably 0.1 mass% or more and 50 mass% or less.
[0106] Since the resin layer (21) is thicker than the low refractive index layer (22), if the functional component is included in the resin layer (21), a high degree of freedom in adjusting the content of the functional component is obtained. On the other hand, if the functional component is included in the low refractive index layer (22), the functional component is distributed near the surface of the optical film (10B), so it is easy to obtain a high antibacterial and antiviral effect.
[0107] When the resin layer (21) contains a functional component, the functional component acts on bacteria or viruses by passing through the low refractive index layer (22) and leaching out from the surface of the optical film (10B). Therefore, it is preferable that the low refractive index layer (22) also satisfies at least one of the first condition and the second condition, and it is also preferable that the resin component of the low refractive index layer (22) satisfies the condition described in the first example with respect to the composition ratio Rc.
[0108] The low refractive index layer (22) is formed by applying a low refractive index layer coating solution, which is a coating solution for forming the low refractive index layer (22), to the upper surface of the resin layer (21), and curing the film formed thereby. The low refractive index layer coating solution includes auxiliary agents as needed, such as a compound for forming the resin component of the low refractive index layer (22) and a polymerization initiator, and additionally includes a refractive index adjusting agent or a functional component depending on the composition of the low refractive index layer (22).
[0109] Known methods such as bar coating, spin coating, offset coating, gravure coating, roll coating, and die coating can be used for the application of the low refractive index layer coating solution. The curing method of the film after coating can be any method according to the curing type of the resin component, and ultraviolet irradiation or heat drying is used.
[0110] [Characteristics of Optical Films]
[0111] As characteristics of the optical film (10), optical properties, mechanical properties, and elemental composition are described. Each of the following characteristics is common to the optical films of the first example and the second example.
[0112] <Optical Properties>
[0113] If the resin layer (21) does not contain fine particles for light scattering, the haze of the optical film (10) is preferably 3% or less. According to this configuration, high transparency is obtained for the optical film (10), and visibility through the optical film (10) is increased.
[0114] When the resin layer (21) contains fine particles for light scattering, the haze of the optical film (10) is preferably 5% or more and 35% or less. According to this configuration, ambient reflection on the optical film (10) is suppressed, while excessive degradation of visibility through the optical film (10) is suppressed.
[0115] In addition, the above haze is a transmission haze and is measured in accordance with JIS K7136.
[0116] When the resin layer (21) contains fine particles for light scattering, light scattering is obtained. Light scattering can be evaluated using reflection clarity of 1° and 5°. Reflection clarity is the value obtained by subtracting reflection haze (%) from 100. Reflection haze is a parameter indicating the degree of diffusion of reflected light, and is obtained by irradiating light onto the surface of the optical film (10) on a black plate through a slit from a light source position where the angle of incidence with respect to the normal direction of the surface of the optical film (10) is set to about 5.7°, and measuring the intensity distribution of reflected light near the direction of specular reflection at a light receiving position in the direction of specular reflection. The reflection haze at any angle θ centered on the specular reflection direction is the percentage of the average value of the reflection intensity at angle +θ and the reflection intensity at angle -θ relative to the reflection intensity in the specular reflection direction, and the value obtained by subtracting the reflection haze at angle θ from 100 is the reflection clarity at angle θ. The measurement conditions are as follows, and conditions other than those below are measured in accordance with ASTM D5767.
[0117] · Slit width: 1 mm
[0118] · Objective: 16 mm
[0119] · Distance from the surface of the optical film to the light-receiving position: 300 mm
[0120] In the case where the resin layer (21) contains fine particles for light scattering, in the optical film (10), it is preferable that the reflection clarity at an angle θ of 1° is 90 or less, and the reflection clarity at an angle θ of 5° is 60 or more. Accordingly, the reflection component for the observation direction is suppressed, and the reflection component for the vicinity of the observation direction is obtained appropriately. Therefore, since the image projected on the surface of the optical film (10) is appropriately blurred, good light-reflecting properties are obtained.
[0121] <Machine Characteristics>
[0122] The pencil hardness of the surface of the optical film (10), that is, the scratch hardness using the pencil method, is preferably 2H or higher. If the pencil hardness is 2H or higher, the surface of the optical film (10) becomes less susceptible to damage. The pencil hardness is measured in accordance with JIS K5600-5-4.
[0123] <Elemental Composition>
[0124] In the optical film (10), antibacterial or antiviral properties are exhibited when the functional component comes into contact with bacteria or viruses. Therefore, the more the functional component is distributed near the surface of the optical film (10), the higher the antibacterial or antiviral properties obtained. Therefore, by measuring the amount of elements containing the functional component near the surface of the optical film (10), the antibacterial or antiviral properties of the optical film (10) can be evaluated simply without conducting long-term antibacterial or antiviral tests.
[0125] Below, a preferred composition of the elemental composition related to the surface of the optical film (10) is described for the case where the functional component is a silane coupling agent containing a quaternary ammonium salt in its molecular structure. The quaternary ammonium salt includes, for example, halide ions such as chloride ions.
[0126] In the elemental analysis of the surface of the optical film (10) by X-ray photoelectron spectroscopy (XPS), it is preferable that the elemental concentration of N is 0.80 atm% or more and 4.00 atm% or less, the elemental concentration of Si is 0.75 atm% or more and 4.50 atm% or less, and the elemental concentration of halogen elements is 0.35 atm% or more and 2.90 atm% or less.
[0127] According to the above configuration, since the functional component is sufficiently distributed on the surface of the optical film (10), both antibacterial and antiviral properties are obtained well. On the other hand, because there is an excessive amount of the functional component, bleed-out in the functional layer is suppressed.
[0128] In the elemental analysis of the surface of the optical film (10) by energy dispersive X-ray spectroscopy (EDX), it is preferable that the elemental concentration of Si be 0.20 atm% or more and 1.30 atm% or less, and the elemental concentration of halogen elements be 0.19 atm% or more and 1.40 atm% or less.
[0129] According to the above configuration, since functional components are sufficiently distributed on the surface of the optical film (10) and in its vicinity, both antibacterial and antiviral properties are obtained well. On the other hand, because there are too many functional components, bleed-out in the functional layer is suppressed. According to EDX, since elemental analysis at a deeper location than XPS is possible, analysis is possible that includes functional components that leach out from the vicinity of the surface of the optical film (10) and act on bacteria or viruses.
[0130] It is preferable that the amount of halogen element elution from the surface of the optical film (10) measured using ion chromatography is 4.0 nmol / cm² or more and 55.0 nmol / cm² or less. The above amount of elution is the amount of halide ions eluted per unit area of the surface when the surface of the optical film (10) is in contact with pure water for 24 hours.
[0131] The amount of halogen element leaching indicates whether the quaternary ammonium ions constituting the functional component are easily released from the optical film (10), that is, whether the functional component is easily acted upon by bacteria or viruses, by including the functional component distributed not only near the surface of the optical film (10) but also inside. If the amount of halogen element leaching is within the above range, both antibacterial and antiviral properties are obtained well. On the other hand, since the functional component is not excessively abundant, bleed-out in the functional layer is suppressed.
[0132] The sample used for measuring the amount of halogen element leaching is obtained in the following procedures (a) to (c).
[0133] (a) Prepare a test specimen formed from an optical film (10) into a square shape with sides of 4 cm or more, and drop 0.4 mL of pure water onto the surface of the test specimen, which is the surface of the optical film (10). Then, a polyethylene cover film with sides of 4 cm is attached to the surface of the test specimen after the dropping of pure water. Accordingly, the area of the surface of the test specimen covered by the cover film is uniformly wetted with pure water. Therefore, the measurement area for the leaching of halogen elements is 16 cm².
[0134] (b) The test specimen after the treatment of (a) above is placed in a petri dish, and the petri dish is placed in an environment with a temperature of 35±1 ℃ and a humidity of 90% RH or higher, and allowed to stand for 24 hours.
[0135] (c) After the treatment of (b) above, the surface of the test specimen is washed with 2.5 mL of pure water, and the pure water used for washing is recovered and used as a sample for measuring the amount of halogen element elution.
[0136] In addition, the elemental composition related to the functional component near the surface of the optical film (10) described above can be adjusted according to the content ratio of the functional component in the functional layer, or the presence and content ratio of additives such as leveling agents in the functional layer.
[0137] [Configuration of the display device]
[0138] As shown in FIG. 3, the display device (100) comprises an optical film (10) and a main body (30) having an image display function. The display surface (30S), which is the surface of the main body (30), is a surface on which an image is displayed, such as the surface of a display panel like a liquid crystal panel or an organic EL panel, or the surface of a touch panel laminated to the display panel. The optical film (10) is positioned on the display surface (30S), and the back surface of the optical film (10) is attached to the display surface (30S).
[0139] In particular, when the display surface (30S) is the surface of a touch panel, the user frequently comes into contact with the display device (100), so it is highly beneficial for the optical film (10) to have antibacterial or antiviral properties.
[0140] Specific examples of the display device (100) include a smartphone, tablet terminal, personal computer, portable game console, music player, television, monitor, electronic book viewing terminal, digital camera, head-mounted display, navigation device, copier, fax machine, printer, printer multifunction device, vending machine, automatic teller machine (ATM), personal authentication device, optical communication device, etc.
[0141] [Example]
[0142] The optical film described above will be explained using specific examples and comparative examples.
[0143] (Example 1)
[0144] The following materials were mixed to prepare a resin layer coating solution, which is a coating solution for forming a resin layer. In addition, the description of the mass parts of each material below indicates the ratio of the relative masses of each material.
[0145] · Photopolymerizable compound: Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (Viscot #300, manufactured by Osaka Organic Chemical Industry) 100 parts by mass
[0146] · Photopolymerization initiator: 1-hydroxycyclohexylphenyl ketone (Omnirad 184, manufactured by IGM Resins BV) 5.0 parts by mass
[0147] · Functional ingredient: Quaternary ammonium salt-based antibacterial and antiviral agent (silane coupling agent) (KBM-9418-40, manufactured by Shin-Etsu Chemical Co., Ltd.) 10.0 parts by mass (Details: Active ingredient 4.0 parts by mass, Solvent (methanol) 6.0 parts by mass)
[0148] · Additive: Leveling agent (GRANDIC PC4300, manufactured by DIC) 0.5 parts by mass
[0149] · Solvent: 110 parts by mass of toluene
[0150] A triacetylcellulose film (TJ40, manufactured by Fujifilm) with a thickness of 60 μm was used as a substrate, and the resin layer coating solution was applied to the surface of the substrate using a bar coater. The formed coating film was dried using a dryer at 100°C for 1 minute, and then the coating film was cured by irradiating it with ultraviolet light under a nitrogen atmosphere (oxygen concentration of 500 ppm or less) to form a resin layer. The thickness of the coating film was 5 μm, and ultraviolet light was irradiated using a high-pressure mercury UV device so that the integrated exposure amount was 200 mJ / cm². Accordingly, an optical film of Example 1 having a substrate and a resin layer was obtained.
[0151] (Example 2)
[0152] For Example 1, the optical film of Example 2 was obtained by the same materials and process as Example 1, except that the photopolymerizable compound was changed.
[0153] · Photopolymerizable compounds :
[0154] 70 parts by mass of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (Viscot #300, manufactured by Osaka Organic Chemical Industry)
[0155] 30 parts by mass of a mixture of glycerin diacrylate and glycerin triacrylate (M-920, manufactured by Toa Synthesis)
[0156] (Example 3)
[0157] The optical film of Example 3 was obtained by the same materials and process as Example 1, except that the photopolymerizable compound was changed.
[0158] · Photopolymerizable compounds :
[0159] Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (Viscot #300, manufactured by Osaka Organic Chemical Industry) 40 parts by mass
[0160] Mixture of glycerin diacrylate and glycerin triacrylate (M-920, manufactured by Toa Synthesis) 60 parts by mass
[0161] (Example 4)
[0162] For Example 1, the optical film of Example 4 was obtained by the same materials and process as Example 1, except that the following material was added to the resin layer coating solution.
[0163] · Organic microparticles (SSX-2035, manufactured by Techpolymer) 6.0 parts by mass
[0164] (Example 5)
[0165] For Example 3, the optical film of Example 5 was obtained by the same materials and process as Example 3, except that the following material was added to the resin layer coating solution.
[0166] · Organic microparticles (SSX-2035, manufactured by Techpolymer) 6.0 parts by mass
[0167] (Example 6)
[0168] The optical film of Example 6 was obtained by the same materials and process as Example 1, except that the photopolymerizable compound was changed.
[0169] · Photopolymerizable compounds :
[0170] 100 parts by mass of a mixture of glycerin diacrylate and glycerin triacrylate (M-920, manufactured by Toa Synthesis)
[0171] (Example 7)
[0172] An optical film of Example 7 was obtained by the same materials and process as Example 1, except that the amount of functional component added to the resin layer coating solution was changed to 20.0 parts by mass, and no leveling agent additive was added to the resin layer coating solution.
[0173] (Example 8)
[0174] An optical film of Example 8 was obtained by the same materials and process as Example 1, except that the functional component was changed to be a leveling agent and no additive was added to the resin layer coating solution.
[0175] · Functional ingredient: Quaternary ammonium salt-based antibacterial and antiviral agent (silane coupling agent) (POLON-V8, manufactured by Shin-Etsu Chemical Co., Ltd.) 30.0 parts by mass
[0176] (Example 9)
[0177] For Example 1, an optical film of Example 9 was obtained using the same materials and process as Example 1, except that no leveling agent additive was added to the resin layer coating solution.
[0178] (Example 10)
[0179] An optical film of Example 10 was obtained by the same materials and process as Example 1, except that the functional component was changed to be the same and no leveling agent additive was added to the resin layer coating solution.
[0180] · Functional ingredient: Quaternary ammonium salt-based antibacterial and antiviral agent (silane coupling agent) (POLON-V8, manufactured by Shin-Etsu Chemical Co., Ltd.) 10.0 parts by mass
[0181] (Comparative Example 1)
[0182] The optical film of Comparative Example 1 was obtained by the same materials and process as Example 1, except that the photopolymerizable compound was changed to be used and no leveling agent was added to the resin layer coating solution.
[0183] · Photopolymerizable compounds :
[0184] 100 parts by mass of dipentaerythritol polyacrylate (NK ester A-DPH, manufactured by Shinnakamura Chemical Industry)
[0185] (Comparative Example 2)
[0186] For Example 1, the optical film of Comparative Example 2 was obtained using the same materials and process as Example 1, except that the photopolymerizable compound was changed.
[0187] · Photopolymerizable compounds :
[0188] Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (Viscot #300, manufactured by Osaka Organic Chemical Industry) 32 parts by mass
[0189] Dipentaerythritol polyacrylate (NK ester A-DPH, manufactured by Shinnakamura Chemical Industry) 68 parts by mass
[0190] (Comparative Example 3)
[0191] For Comparative Example 2, the optical film of Comparative Example 3 was obtained using the same materials and process as Comparative Example 2, except that the following material was added to the resin layer coating solution.
[0192] · Organic microparticles (SSX-2035, manufactured by Techpolymer) 6.0 parts by mass
[0193] (Comparative Example 4)
[0194] For Example 1, the optical film of Comparative Example 4 was obtained using the same materials and process as Example 1, except that the functional component was changed.
[0195] · Functional ingredient: Silver-based antibacterial and antiviral agent (PTC-NT ANV additive ST, manufactured by Dainichi Seika Kogyo) 5.0 parts by mass
[0196] (Comparative Example 5)
[0197] The optical film of Comparative Example 5 was obtained using the same materials and process as Example 1, except that the amount of functional component added to the resin layer coating solution was changed to 50.0 parts by mass.
[0198] (Evaluation Method)
[0199] <Water Vapor Permeability>
[0200] In accordance with JIS Z0208 (Method for testing moisture permeability of moisture-proof packaging materials (Cup method)), water vapor permeability was measured for the optical films and substrates of each example and each comparative example under conditions of temperature: 40 ℃, humidity: 90 % RH, and test time: 24 hours. Then, using (Equation 1) and (Equation 2) described in the above embodiment, the water vapor permeability Wx per unit film thickness in the resin layer of each example and each comparative example was calculated.
[0201] Pencil Hardness
[0202] For the optical films of each example and each comparative example, the pencil hardness of the optical film surface was measured by conducting a hardness test in accordance with JIS K5600-5-4 using a pencil (uni, manufactured by Mitsubishi Pencil) and a Clemens-type scratch hardness tester (HA-301, manufactured by Tester Industry) under conditions of a load of 750 g and a scratching speed of 0.5 mm / sec. In the measurement, the test was repeated while changing the hardness of the pencil, and the surface of the optical film was observed visually; the maximum hardness at which no scratch was observed was taken as the measurement result.
[0203] <Heize>
[0204] For each example and each comparative example, haze was measured. The haze measurement was performed in accordance with JIS K7136 using a haze meter (NDH7000, manufactured by Nippon Denshoku Kogyo).
[0205] <Bleed Out>
[0206] For each example and each comparative example, the surface of the optical film was rubbed with a nonwoven fabric (Benkot M-3 II, manufactured by Asahi Kasei), and the condition of the surface was observed. As an evaluation of whether bleed-out occurred, a case where there was no change in the appearance of the surface before and after rubbing was rated as good “S,” and a case where a change such as a change in haze or the occurrence of scratches occurred in the appearance of the surface after rubbing was rated as poor “F.”
[0207] <Bang Hyeon-seong>
[0208] For the optical films of each example and each comparative example, the anti-glare properties were evaluated by measuring the reflection clarity at 1° and the reflection clarity at 5°. Each reflection clarity was measured under the following conditions using a display measurement system (manufactured by DM&S: SMS-1000) on an optical film with its back side attached to a black plate with an optical adhesive. In addition, measurements other than those below were performed in accordance with ASTM D5767.
[0209] · Width of the light source slit: 1 mm
[0210] · Objective: 16 mm
[0211] · Distance between the surface of the optical film and the light-receiving camera: 300 mm
[0212] In the evaluation of reflection clarity, a case where the reflection clarity at 1° is 90 or less and the reflection clarity at 5° is 60 or more is classified as good “S”, and a case where at least one of the cases where the reflection clarity at 1° is greater than 90 and the reflection clarity at 5° is less than 60 is classified as poor “F”. The poor includes cases corresponding to a state where the surrounding image is clearly reflected on the optical film and cases corresponding to a state where the image reflected on the optical film is excessively blurred.
[0213] <XPS Analysis>
[0214] For Examples 1, 7 to 10 and Comparative Example 5, elemental analysis by XPS was performed on the surface of the optical film using an X-ray photoelectron spectrometer (Quantum 2000, manufactured by ALVAC PI). The measurement conditions are shown below.
[0215] X-line: Monochromatic Al-Kα line
[0216] X-ray output: 25 W 15 kV
[0217] Photoelectron entry angle: 45°
[0218] <EDX Analysis>
[0219] For Examples 1, 7 to 10 and Comparative Example 5, elemental analysis by EDX was performed on the surface of the optical film using a scanning electron microscope-energy dispersive X-ray analyzer (SU-8020, manufactured by Hitachi High Technologies).
[0220] <Ion Chromatography Analysis>
[0221] For Examples 1, 7 to 10 and Comparative Example 5, quantification of chloride ions by ion chromatography was performed on the eluent from the surface of the optical film using an ion chromatograph analysis device (DX-500, manufactured by Dionex). An anion exchange column (manufactured by Dionex, stationary phase: IonPac AS11-HC-4㎛) was used as the column, and a KOH solution was used as the glass solution. The sample used to measure the amount of chloride ions eluted from the eluent was obtained through the procedures (a) to (c) described in the above embodiments.
[0222] <Antibacterial properties>
[0223] For the optical films of each example and each comparative example, an antibacterial test was conducted against Staphylococcus aureus and Escherichia coli, respectively, in accordance with JIS Z 2801. As the unprocessed sample, a film from which the functional component was excluded from the example or comparative example was used. In the evaluation of antibacterial properties, if the antibacterial activity value against both Staphylococcus aureus and Escherichia coli was 2.0 or higher, it was classified as "S" (Good), and if the antibacterial activity value against at least one of Staphylococcus aureus and Escherichia coli was less than 2.0, it was classified as "F" (Poor).
[0224] <Antiviral>
[0225] For the optical films of each example and each comparative example, an antiviral test against influenza A virus and feline calicivirus was performed in accordance with ISO 21702. As the unprocessed sample, a film from which the functional component was excluded from the subject example or comparative example was used. In the evaluation of antiviral properties, if the antibacterial activity value against at least one of influenza A virus and feline calicivirus was 2.0 or higher, it was classified as "S" (Good), and if the antibacterial activity value against both influenza A virus and feline calicivirus was less than 2.0, it was classified as "F" (Poor).
[0226] (Evaluation Results)
[0227] Table 1 shows, for each example and each comparative example, the average hydroxyl group Hv (mgKOH / g) of the resin component of the resin layer, the water vapor permeability Wx ((g / m²·day) / ㎛) per unit film thickness of the resin layer, the composition ratio Rc, the type and amount of functional component, the presence or absence of light-scattering microparticles, and the results of each evaluation item. The average hydroxyl group Hv was calculated from the hydroxyl group of the material monomer. The composition ratio Rc was calculated from the mole fraction of the material monomer. The evaluation items are pencil hardness, haze (%), presence or absence of bleed-out, antifungal properties, antibacterial properties, and antiviral properties. The evaluation of antifungal properties was conducted on Examples 4, 5, and Comparative Example 3, which contain light-scattering microparticles for the purpose of expressing antifungal properties. In addition, for Examples 7, 8, 10, and Comparative Example 5, some items were not evaluated.
[0228] In addition, Table 2 shows the results of elemental analysis by XPS, EDX, and ion chromatography (IC), respectively. Also, Table 2 shows the evaluation results of antibacterial and antiviral properties.
[0229]
[0230]
[0231] As shown in Table 1, in Examples 1 to 10, where the average hydroxyl group of the resin component has an Hv of 100 mgKOH / g or higher, bleed-out is suppressed even if the functional component is organic. On the other hand, in Comparative Examples 1 to 3, where the average hydroxyl group of the resin component has an Hv of less than 100 mgKOH / g and the functional component is organic, bleed-out occurs. Additionally, in Comparative Example 5, where the amount of added functional component is 50 mass% of the resin component, bleed-out also occurs.
[0232] [This part is a misreading of the text].
[0233] From Table 1, it can be confirmed that there is a correlation between the water vapor permeability Wx per unit film thickness of the resin layer and the average hydroxyl group of the resin component Hv. In Examples 1 to 10, where bleed-out is suppressed, the water vapor permeability Wx is 170 (g / m²·day) / ㎛ or higher. On the other hand, in Comparative Examples 1 to 3, where bleed-out occurs, the water vapor permeability Wx is less than 170 (g / m²·day) / ㎛.
[0234] From the above, it was confirmed that by using an organic functional component and a resin component with an average hydroxyl group Hv of 100 mgKOH / g or more, at least antibacterial properties can be obtained while suppressing the degradation of optical properties and the occurrence of bleed-out.
[0235] In addition, it was confirmed that by using organic functional components and having a water vapor permeability Wx of 170 (g / m²·day) / ㎛ or higher in the resin layer, at least antibacterial properties can be obtained while suppressing the degradation of optical properties and the occurrence of bleed-out.
[0236] In addition, among the examples, in Example 6, where the average hydroxyl group of the resin component has an Hv of more than 200 mgKOH / g, the pencil hardness is lower compared to other examples. Therefore, in order to suppress the deterioration of mechanical properties, it is desirable that the average hydroxyl group of the resin component has an Hv of 200 mgKOH / g or less. Likewise, from Example 6, in order to suppress the deterioration of mechanical properties, it is desirable that the water vapor permeability Wx is 450 (g / m²·day) / ㎛ or less.
[0237] In addition, from the perspective of composition ratio Rc, it was confirmed that if composition ratio Rc is 0.40 or higher, bleed-out is suitably suppressed, and if composition ratio Rc is 0.85 or lower, good hardness is obtained.
[0238] As shown in Table 2, in Examples 1, 7, and 8, which have good antibacterial and antiviral properties, the elemental concentration of N is 0.80 atm% or higher in the elemental analysis by XPS, the elemental concentration of Si is 0.75 atm% or higher, and the elemental concentration of Cl is 0.35 atm% or higher. On the other hand, in Examples 9 and 10, where at least one of these elemental concentrations falls below the above range, antibacterial properties are obtained, but antiviral properties are not sufficient.
[0239] In addition, in Examples 1, 7, and 8, in the elemental analysis by EDX, the elemental concentration of Si is 0.20 atm% or higher, and the elemental concentration of Cl is 0.19 atm% or higher. On the other hand, in Examples 9 and 10, these elemental concentrations are below the above range.
[0240] In addition, in Examples 1, 7, and 8, the amount of Cl elution in the elemental analysis by ion chromatography is 4.0 nmol / cm² or more. On the other hand, in Examples 9 and 10, the amount of Cl elution is below the above range.
[0241] Therefore, as the results of each elemental analysis fall within the above range, it was confirmed that both antibacterial and antiviral properties are obtained in good condition.
[0242] In addition, in Examples 1, 7, and 8, in the elemental analysis by XPS, the elemental concentration of N is 4.00 atm% or less, the elemental concentration of Si is 4.50 atm% or less, and the elemental concentration of Cl is 2.90 atm% or less, but in Comparative Example 5, where these elemental concentrations exceed the above range, bleed-out occurs.
[0243] In addition, in Examples 1, 7, and 8, in the elemental analysis by EDX, the elemental concentration of Si is 1.30 atm% or less, and the elemental concentration of Cl is 1.40 atm% or less. On the other hand, in Comparative Example 5, these elemental concentrations exceed the above range.
[0244] In addition, in Examples 1, 7, and 8, the amount of Cl eluted by elemental analysis by ion chromatography is 55.0 nmol / cm² or less. On the other hand, in Comparative Example 5, the amount of Cl eluted exceeds the above range.
[0245] Therefore, it was confirmed that the occurrence of bleed-out caused by excess functional components is suppressed, as the results of each elemental analysis are within the above range.
[0246] According to the above embodiments and examples, the effects listed below can be obtained.
[0247] (1) The functional layer contains an organic functional component and a resin component having an average hydroxyl group Hv of 100 mgKOH / g or more. Accordingly, at least one of antibacterial and antiviral properties can be obtained, and the increase in haze and the occurrence of bleed-out can be suppressed.
[0248] (2) The functional layer contains organic functional components and resin components, and the water vapor permeability per unit film thickness in the functional layer is 170 (g / m²·day) / ㎛ or more. Accordingly, at least one of antibacterial and antiviral properties can be obtained, and the increase in haze and the occurrence of bleed-out can be suppressed.
[0249] (3) By having an average hydroxyl value of the resin component of 200 mgKOH / g or less, the deterioration of mechanical properties in the functional layer can be suppressed.
[0250] (4) By having a composition ratio Rc of 0.40 or higher in the resin component, the occurrence of bleed-out can be preferably suppressed. In addition, by having a composition ratio Rc of 0.85 or lower in the resin component, the deterioration of mechanical properties can be suitably suppressed.
[0251] (5) High transparency can be obtained if the haze of the optical film is 3% or less. Also, since the functional component is organic, it is easy to reduce the haze to 3% or less.
[0252] (6) If the optical film is composed of fine particles for light scattering, an optical film with good anti-glare properties can be realized. Also, if the haze of the optical film is 5% or more and 35% or less, good anti-glare properties can be obtained. In addition, if the reflection clarity of the optical film at 1° is 90 or less and the reflection clarity at 5° is 60 or more, good anti-glare properties can be obtained.
[0253] (7) If the average particle size of the fine particles for light scattering is 30% or more of the resin layer thickness, the effect of light scattering by the fine particles can be appropriately obtained.
[0254] (8) If the content ratio of fine particles for light scattering in the resin layer is 3.0 mass% or more and 20 mass% or less, the effect of light scattering by fine particles can be appropriately obtained and the deterioration of the mechanical properties of the resin layer can be suppressed.
[0255] (9) If the pencil hardness of the surface of the optical film is 2H or higher, good mechanical properties can be obtained.
[0256] (10) If the thickness of the resin layer is 1.0 μm or more, the uniformity of the resin layer thickness, the porosity of the coating solution for forming the resin layer, the mechanical strength of the resin layer, and the antibacterial or antiviral activity when the resin layer is a functional layer can be increased.
[0257] (11) If the thickness of the low refractive index layer is 30 nm or more and 300 nm or less, it is easy to generate light interference and also easy to obtain good scratch resistance and adhesion to the resin layer.
[0258] (12) If the functional component is a silane coupling agent containing a quaternary ammonium salt in its molecular structure, it is suitable as a functional component of an organic system.
[0259] (13) In the elemental analysis of the surface of the optical film by XPS, the elemental concentration of N is 0.80 atm% or more and 4.00 atm% or less, the elemental concentration of Si is 0.75 atm% or more and 4.50 atm% or less, and the elemental concentration of halogen elements is 0.35 atm% or more and 2.90 atm% or less. According to this composition, both antibacterial and antiviral properties can be obtained well, while bleed-out in the functional layer can be suppressed.
[0260] (14) In the elemental analysis of the surface of the optical film by EDX, the elemental concentration of Si is 0.20 atm% or more and 1.30 atm% or less, and the elemental concentration of halogen elements is 0.19 atm% or more and 1.40 atm% or less. According to this composition, both antibacterial and antiviral properties can be obtained well, while bleed-out in the functional layer can be suppressed.
[0261] (15) The amount of halogen element leached from the surface of the optical film, measured using ion chromatography, is 4.0 nmol / cm² or more and 55.0 nmol / cm² or less. According to this composition, both antibacterial and antiviral properties can be obtained well, while bleed-out in the functional layer can be suppressed.
[0262] (16) By providing an optical film to a display device, good optical and mechanical properties can be obtained along with antibacterial and antiviral properties near the surface of the display device. In particular, if the display device is equipped with a touch panel, the benefits of the optical film having antibacterial and antiviral properties can be obtained to a high degree.
[0263] Additionally, the expression “at least one” used in this specification means “one or more” of the desired options. For example, the expression “at least one” used in this specification means “only one option” or “both of the two options” if the number of options is two. As another example, the expression “at least one” used in this specification means “only one option” or “a combination of two or more arbitrary options” if the number of options is three or more. Explanation of the symbols
[0264] 10, 10A, 10B: Optical film 20 : Entry 21 : Resin layer 22 : Low refractive index layer 100 : Display device
Claims
Claim 1 An optical film comprising a substrate and a functional layer containing a functional component which is at least one of an antibacterial agent and an antiviral agent and a resin component, wherein the functional component is an organic material, the ratio of the functional component to the resin component contained in the functional layer is 40 mass% or less, the average hydroxyl value of the resin component is 100 mgKOH / g or more, the first condition is that the water vapor transmittance per unit film thickness in the functional layer is 170 (g / m²·day) / ㎛ or more, and the optical film satisfies at least one of the first condition and the second condition. Claim 2 An optical film according to claim 1, satisfying the first condition and having an average hydroxyl value of the resin component of 200 mgKOH / g or less. Claim 3 An optical film according to claim 1, wherein the constituent unit of the polymer contained in the resin component comprises a first constituent unit not having a hydroxyl group and a second constituent unit having one or more hydroxyl groups, and the ratio of the second constituent unit to all constituent units in the resin component is 0.40 or more. Claim 4 In claim 1, the haze of the optical film is 3% or less, an optical film. Claim 5 In claim 1, the optical film comprises a resin layer supported on the substrate, the functional layer comprises the resin layer, and the resin layer comprises fine particles for light scattering. Claim 6 An optical film according to claim 5, wherein the average particle size of the fine particles is 30% or more of the resin layer thickness. Claim 7 An optical film according to claim 5, wherein the content ratio of the fine particles in the resin layer is 3.0 mass% or more and 20 mass% or less. Claim 8 In claim 1, the optical film has a pencil hardness of 2H or higher on the surface of the optical film. Claim 9 In claim 1, the haze of the optical film is 5% or more and 35% or less. Claim 10 An optical film according to claim 1, wherein the reflection clarity at 1° is 90 or less and the reflection clarity at 5° is 60 or more. Claim 11 The optical film according to claim 1, wherein the optical film comprises a resin layer supported on the substrate, the functional layer comprises the resin layer, and the thickness of the resin layer is 1.0 μm or more. Claim 12 The optical film according to claim 1, wherein the optical film comprises a resin layer supported on a substrate and a low-refractive-index layer covering the resin layer on the side opposite to the substrate with respect to the resin layer, the functional layer comprising at least the resin layer among the resin layer and the low-refractive-index layer, and the thickness of the low-refractive-index layer is 30 nm or more and 300 nm or less. Claim 13 An optical film according to any one of claims 1 to 12, wherein the functional component is a silane coupling agent comprising a quaternary ammonium salt in its molecular structure, and the quaternary ammonium salt comprises a halide ion. Claim 14 In claim 13, the optical film has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and in elemental analysis of the first surface by X-ray photoelectron spectroscopy, the elemental concentration of N is 0.80 atm% or more and 4.00 atm% or less, the elemental concentration of Si is 0.75 atm% or more and 4.50 atm% or less, and the elemental concentration of a halogen element is 0.35 atm% or more and 2.90 atm% or less. Claim 15 In claim 13, the optical film has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and in elemental analysis of the first surface by energy-dispersive X-ray spectroscopy, the elemental concentration of Si is 0.20 atm% or more and 1.30 atm% or less, and the elemental concentration of a halogen element is 0.19 atm% or more and 1.40 atm% or less. Claim 16 In claim 13, the optical film has a first surface and a second surface which is a surface opposite to the first surface and is a surface having the substrate, and the amount of halogen element elution from the first surface measured using ion chromatography is 4.0 nmol / cm² or more and 55.0 nmol / cm² or less. Claim 17 A display device comprising an optical film described in any one of claims 1 to 12, wherein the optical film is positioned on a display surface on which an image is displayed.
